Fecal microbiome in systemic sclerosis, in search for the best candidate for microbiota-targeted therapy for small intestinal bacterial overgrowth control. Issue 3 (October 2022) - Fiorentini, Elisa; Russo, Edda; Amedei, Amedeo; Bellando Randone, Silvia
Gastrointestinal involvement is a common complication in systemic sclerosis patients and must be suspected and investigated already in the early stages of the disease. Gastrointestinal symptoms and complications—such as gastroesophageal reflux disease, intestinal pseudo-obstruction, malnutrition, diarrhea, constipation, and small intestinal bacterial overgrowth—severely impair systemic sclerosis patients' quality of life and affect their prognosis. Although some pathogenetic aspects of the gastrointestinal involvement in systemic sclerosis remain unclear, defining the characteristics of the microbiota and its role could help in risk stratification, selection of candidates for microbiota-targeted therapies, prediction of standard treatment efficacy, and prognosis of systemic sclerosis patients. Finally, understanding how to modify the microbiota composition may represent an important therapeutic approach to target gastrointestinal involvement in systemic sclerosis.